Trend Coffee Shop Pada Konsumen Remaja Berperilaku FOMO Di Kelurahan Pulo Gebang - Alyya Haliza Maharani; Martini Martini; Hidayath, A.N (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
Coffee is a commodity in the world that is cultivated in more than 50 countries. Historically, coffee was first found in Ethiopia, where it was planted in the highlands. At that time, many people on the African continent, especially Ethiopians, consumed coffee beans. The coffee tree which then produces coffee beans is then roasted and ground into a coffee drink. Several regions in Indonesia are known as the world's best coffee producers. In Indonesia itself, there are two types of coffee plants, namely Robusta coffee (Coffea canephora) and Arabica coffee (Coffea arabica). These two types of coffee have different tastes and aromas depending on the region of origin. Several regions in Indonesia are considered the best coffee producing regions in the world. Lampung is known as the largest coffee producer in Indonesia which offers Robusta coffee. On the island of Sumatra there are quality types of coffee that are well known in various countries, for example Sidikalang coffee from North Sumatra, Mandailing coffee and Gayo coffee from Aceh, South Sumatra coffee and so on. Apart from Sumatra Island, the island also has quality types of coffee such as Malang coffee which is similar to the coffee in Lampung, Bali coffee and many other types of coffee.